From TPACK to N-TPACK Framework for Vocational Education and Training With a Focus on Nutritional Science and Home Economics - Carmen Torggler; Susanne Miesera; Claudia Nerdel (International Journal for Research in Vocational Education and Training, 2023)
Context: In Germany, vocational education and training (VET) plays a key role in the transition from school to working life. Due to its proximity to the labour market and an increasingly digitised, connected world, the professional knowledge requirements of VET teachers are changing and an adjustment of competence frameworks for vocational teachers is needed.